Aqueous positive electrode edge coating glue and application thereof, and positive electrode plate edge coating slurry
By using water-based positive electrode side coating glue, the cost increase and material leakage problems caused by PVDF glue are solved. Acrylic polymers and water are used as solvents to prepare side coating materials with strong adhesion and good toughness, which improves the safety and production efficiency of lithium batteries.
Patent Information
- Application Number
- CN202410304506.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2025-09-19
AI Technical Summary
The existing positive electrode edge coating uses PVDF glue, which leads to cost increases and material leakage. In addition, the traditional coating method uses NMP solvent, which is costly, highly toxic, and difficult to recycle, affecting the safety and production efficiency of lithium batteries.
A water-based positive electrode edge coating glue is used, which contains polymer latex particles with a grafted polymer as the main chain, acrylic polymer as the main component, and water as the solvent to prepare an edge coating material with good adhesion and toughness.
The invention reduces production costs, improves the safety and production efficiency of lithium batteries, avoids material channeling, and the coating is not easy to fall off after being immersed in the electrolyte, so it is suitable for industrial production.
Smart Images

Figure BDA0004745350510000061 
Figure BDA0004745350510000071 
Figure BDA0004745350510000081
Abstract
Description
Technical Field
[0001] The invention relates to a water-based positive electrode side coating glue and application thereof and a positive electrode plate side coating slurry, belonging to the technical field of battery adhesives. Background Art
[0002] With the development of the new energy industry, research on lithium battery technology has become a hot topic. While pursuing high energy density and long life, the safety performance of lithium batteries has also become a top priority. To this end, some researchers have developed positive electrode edge coating technology. This technology reduces economic losses while also providing safety by coating the edge of the positive electrode with a layer of economical insulating material. In addition to reducing short circuits between the aluminum and the negative electrode material, it also reduces die-cutting burrs and mitigates the risk of heat generation at the base of the tab, which can lead to thermal shrinkage of the diaphragm. Currently, positive electrode edge coatings are primarily composed of boehmite and PVDF. However, the binder used in positive electrode edge coatings is primarily PVDF glue. As PVDF prices continue to rise, the cost of edge coatings is also increasing. Moreover, since the positive electrode material also uses PVDF glue as a binder, material cross-contamination is prone to occur at the interface between the positive electrode material and the edge coating in the positive electrode sheet, resulting in poor process performance.
[0003] Furthermore, traditional coating processes are characterized by harsh processing environments, high costs, difficulty in recycling, and toxicity of the NMP solvent. This has led researchers to consider adopting a green, low-cost, water-based coating method, using water as the solvent. Water is cheaper than NMP, safer, and more environmentally friendly. Furthermore, it eliminates the need for harsh processing environments during electrode preparation, further simplifying the production process and reducing costs. Summary of the Invention
[0004] In view of the above defects, the technical problem solved by the present invention is to provide a water-based positive electrode edge coating glue.
[0005] The water-based positive electrode side coating of the present invention comprises a grafted polymer, wherein the grafted polymer has an acrylic polymer as the main chain and is grafted with polymer latex particles, and the weight percentage of the polymer latex particles in the grafted polymer is 20 to 80%. The polymerization monomers of the acrylic polymer include acrylic acid monomers, acrylamide monomers and hydroxyalkyl acrylate monomers; the polymerization monomers of the polymer latex particles include a cross-linking monomer and a double bond monomer, and the double bond monomer includes (meth) alkyl acrylate and at least one of styrene, p-fluorostyrene, methylstyrene, m-fluorostyrene, o-fluorostyrene, p-methoxystyrene, o-methylstyrene, p-methylstyrene, acrylonitrile and methacrylonitrile.
[0006] In some embodiments, the weight percentage of the polymer latex particles to the graft polymer is 20% to 50%.
[0007] In some specific embodiments, the weight percentage of the polymer latex particles to the graft polymer is 30%.
[0008] In some specific embodiments, the acrylic monomer includes at least one of acrylic acid, methacrylic acid, allyloxyhydroxypropyl sulfonic acid, vinyl sulfonic acid, 2-propylene amino-2-methylpropane sulfonic acid, propylene sulfonic acid, methpropylene sulfonic acid, itaconic acid, and maleic acid;
[0009] The acrylamide monomer includes at least one of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, 2-methacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide;
[0010] The hydroxyalkyl acrylate monomer includes at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 3-(4-hydroxyphenoxy)propyl acrylate, 3-(perfluoro-3-methylbutyl) 2-hydroxypropyl acrylate, and 3-perfluorooctyl 2-hydroxypropyl acrylate;
[0011] The cross-linking monomer includes at least one of ethylene glycol dimethacrylate, ethylene glycol diacrylate, allyl methacrylate, allyl acrylate, N,N-methylenebisacrylamide, and N,N'-methylenebismethylacrylamine;
[0012] The (meth)acrylic acid alkyl ester includes at least one of n-butyl acrylate, n-butyl methacrylate, n-octyl acrylate, isooctyl acrylate, lauryl methacrylate, lauryl acrylate, octadecyl methacrylate, octadecyl acrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, isobornyl acrylate, vinyl acetate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, and glycidyl methacrylate.
[0013] In one embodiment of the present invention, the weight ratio of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers is 15-70:1-10:10-30. In a specific embodiment of the present invention, the weight ratio of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers is 30-70:1-10:10-20. In a specific example, the weight ratio of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers is 57:3:15.
[0014] In one embodiment of the present invention, the aqueous positive electrode edge coating glue further comprises a solvent. Preferably, the solvent is water.
[0015] In a specific embodiment of the present invention, the aqueous positive electrode side coating glue has a viscosity of 80 to 10,000 cp when measured at 25° C. based on a solid content of 30%.
[0016] The present invention also provides the use of the water-based positive electrode edge coating glue of the present invention in the edge coating of positive electrode plates.
[0017] The water-based positive electrode edge coating glue of the present invention can be applied to the edge coating of positive electrode plates, has good adhesion to aluminum foil, and has certain toughness. It does not leak when folded 180 degrees, and is not easy to fall off when wiped after being soaked in electrolyte.
[0018] The present invention also provides a positive electrode plate edge coating slurry.
[0019] The positive electrode edge coating slurry of the present invention comprises a ceramic material and an adhesive, wherein the adhesive is the water-based positive electrode edge coating glue of the present invention.
[0020] In some specific embodiments, the ceramic material is selected from at least one of alumina, boehmite, magnesium oxide, and magnesium hydroxide.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The water-based positive electrode edge coating glue of the present invention can be used as the positive electrode plate edge coating glue, has good adhesion to aluminum foil, the plate will not fall off when pulled by tape, and has certain toughness, will not leak when folded 180 degrees, and will not fall off easily when wiped after being soaked in electrolyte.
[0023] The water-based positive electrode edge coating glue of the present invention has a simple preparation method, is green and environmentally friendly, and is applicable to industrial production. DETAILED DESCRIPTION
[0024] The water-based positive electrode side coating of the present invention comprises a grafted polymer, wherein the grafted polymer has an acrylic polymer as the main chain and is grafted with polymer latex particles, and the weight percentage of the polymer latex particles in the grafted polymer is 20 to 80%. The polymerization monomers of the acrylic polymer include acrylic acid monomers, acrylamide monomers and hydroxyalkyl acrylate monomers; the polymerization monomers of the polymer latex particles include a cross-linking monomer and a double bond monomer, and the double bond monomer includes (meth) alkyl acrylate and at least one of styrene, p-fluorostyrene, methylstyrene, m-fluorostyrene, o-fluorostyrene, p-methoxystyrene, o-methylstyrene, p-methylstyrene, acrylonitrile and methacrylonitrile.
[0025] The water-based positive electrode edge coating glue of the present invention has an acrylic polymer as the main chain and is grafted with a certain amount of polymer latex particles. It can be used as the positive electrode edge coating glue, has good adhesion to aluminum foil, and has certain toughness. It can withstand 180° folding and is resistant to electrolyte erosion. It is not easy to fall off when wiped after being soaked in electrolyte and has high wet adhesion.
[0026] In the present invention, the hydroxyalkyl acrylate monomer contained in the polymer with acrylic acid polymer as the main chain has excellent dispersibility and adhesion properties to boehmite.
[0027] In the present invention, the weight percentage of the polymer latex particles in the graft polymer is the key. In one embodiment of the present invention, the weight percentage of the polymer latex particles in the graft polymer is 20-80%. If the weight percentage of the polymer latex particles is too large or too small, the edge coating performance will be affected.
[0028] In some embodiments, the weight percentage of the polymer latex particles to the graft polymer is 20% to 50%.
[0029] In some specific embodiments, the weight percentage of the polymer latex particles to the grafted polymer is 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0030] The graft copolymer of the present invention is a component that plays a bonding role in water-based positive electrode side coating. The graft polymer has an acrylic polymer as the main chain and grafted polymer latex particles.
[0031] The acrylic polymer of the present invention comprises acrylic acid monomers, acrylamide monomers and hydroxyalkyl acrylate monomers.
[0032] Among them, the acrylic monomer is a substance containing a double bond and a carboxyl group, including but not limited to at least one of acrylic acid, methacrylic acid, allyloxyhydroxypropyl sulfonic acid, vinyl sulfonic acid, 2-propyleneamine-2-methylpropanesulfonic acid, propylene sulfonic acid, methpropylene sulfonic acid, itaconic acid, and maleic acid.
[0033] Acrylamide monomers are substances containing double bonds and amide groups, including but not limited to at least one of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, 2-methylacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide.
[0034] The hydroxyalkyl acrylate monomer is a substance containing a double bond and a hydroxyl group, including but not limited to at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 3-(4-hydroxyphenoxy)propyl acrylate, 3-(perfluoro-3-methylbutyl) 2-hydroxypropyl acrylate, and 3-perfluorooctyl 2-hydroxypropyl acrylate.
[0035] The ratios of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers can be conventionally used in the art. In one embodiment of the present invention, the weight ratio of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers is 15-70:1-10:10-30. In a specific embodiment of the present invention, the weight ratio of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers is 30-70:1-10:10-20. In a specific example, the weight ratio of acrylic acid monomers, acrylamide monomers, and hydroxyalkyl acrylate monomers is 57:3:15.
[0036] Polymer latex particles are tiny particles formed during the emulsion polymerization process. These particles are formed from monomers through free radical polymerization or ionic polymerization. The monomers for polymerizing the polymer latex particles can be hydrophobic monomers containing double bonds commonly used in the art. In one embodiment of the present invention, the monomers for polymerizing the polymer latex particles include a crosslinking monomer and a monomer containing a double bond.
[0037] The cross-linking monomer has at least two double bonds, including but not limited to at least one of ethylene glycol dimethacrylate, ethylene glycol diacrylate, allyl methacrylate, allyl acrylate, N,N-methylenebisacrylamide, and N,N'-methylenebismethylacrylamine.
[0038] The double bond monomer includes at least one of (meth)acrylate and styrene, p-fluorostyrene, methylstyrene, m-fluorostyrene, o-fluorostyrene, p-methoxystyrene, o-methylstyrene, p-methylstyrene, acrylonitrile, and methacrylonitrile.
[0039] The (meth)acrylate alkyl ester is a substance obtained by the esterification reaction of acrylic acid or methacrylic acid with an alcohol, including but not limited to at least one of n-butyl acrylate, n-butyl methacrylate, n-octyl acrylate, isooctyl acrylate, lauryl methacrylate, lauryl acrylate, octadecyl methacrylate, octadecyl acrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, isobornyl acrylate, vinyl acetate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, and glycidyl methacrylate.
[0040] The water-based positive electrode edge coating of the present invention further comprises a solvent. Preferably, the solvent is water.
[0041] In a specific embodiment of the present invention, the aqueous positive electrode side coating glue has a viscosity of 80 to 10,000 cp when measured at 25° C. based on a solid content of 30%.
[0042] The viscosity described in the present invention is dynamic viscosity, which is measured using a Brookfield viscometer with a temperature controlled at 25° C., a rotor model of 62#, and a rotation speed of 30 r / min.
[0043] The water-based positive electrode side coating glue of the present invention can be prepared by conventional methods. In one embodiment of the present invention, the preparation method of the water-based positive electrode side coating glue of the present invention comprises the following steps:
[0044] The polymerization monomers of the acrylic polymer are mixed to form a droplet A; the polymerization monomers of the polymer latex particles, an emulsifier and water are mixed to form a droplet B;
[0045] Water is used as the reaction system; under a protective atmosphere, the reaction system is heated to the reaction temperature, and then an initiator is added, and dropwise liquid A is added. After reacting for 1 to 10 hours, dropwise liquid B is added and the reaction is continued until the reaction is completed to obtain a water-based positive electrode edge coating.
[0046] In this method, the initiator can be any conventional initiator in the art, and the reaction temperature is related to the type of monomer and can be obtained through routine experiments. In one embodiment of the present invention, the initiator is a peroxide, such as ammonium persulfate, and the reaction temperature is 60-80°C.
[0047] During the polymerization of the polymer latex particles, an emulsifier needs to be added. The emulsifiers commonly used in the art are all suitable for the present invention. In one embodiment, the emulsifier is at least one of sodium lauryl sulfate, sodium lauryl sulfonate, Span, OP-10, sodium dodecylbenzene sulfonate, sodium stearate, SR-10, and Tween 80.
[0048] During the polymerization of the polymer latex particles, an emulsifier needs to be added. Commonly used emulsifiers in the art are suitable for use in the present invention. In one embodiment, the emulsifier is at least one of an alkyl anionic emulsifier, such as sodium lauryl sulfate, sodium lauryl sulfonate, sodium dodecylbenzenesulfonate, and sodium stearate; a nonionic emulsifier, such as the Span series and Tween 80; an alkylphenol polyoxyethylene ether emulsifier, such as OP-10; and a reactive emulsifier, such as SR-10.
[0049] In the present invention, OP-10 is dodecylphenol polyoxyethylene ether, which is a commonly used emulsifier and can be purchased on the market.
[0050] SR-10 is an ammonium salt of allyloxy isomeric alcohol ether sulfate, a commonly used reactive emulsifier available on the market.
[0051] The amount of emulsifier used can be the conventional amount in this field and will not be described in detail here.
[0052] The water-based positive electrode edge coating glue of the present invention can be applied to the edge coating of positive electrode plates, has good adhesion to aluminum foil, and has certain toughness. It does not leak when folded 180 degrees, and is not easy to fall off when wiped after being soaked in electrolyte.
[0053] The positive electrode edge coating slurry of the present invention comprises a ceramic material and an adhesive, wherein the adhesive is the water-based positive electrode edge coating glue of the present invention.
[0054] In some specific embodiments, the ceramic material is selected from at least one of alumina, boehmite, magnesium oxide, and magnesium hydroxide.
[0055] The specific embodiments of the present invention are further described below in conjunction with examples, but the present invention is not limited to the scope of the examples.
[0056] Examples 1 to 15
[0057] 1. Mixing acrylic acid monomer, acrylamide monomer and hydroxyalkyl acrylate to form a mixed dropwise solution A;
[0058] 2. Mix a double bond monomer, a cross-linking monomer, an emulsifier and water to form a mixed dropwise solution B;
[0059] 3. Prepare 75 g of 20% distilled water solution with 15 g of ammonium persulfate;
[0060] 4. Add 2250 g of distilled water to a 5000 mL four-necked flask, flow nitrogen for 15 minutes, and then heat to 65°C;
[0061] 5. When the temperature of the liquid in the four-necked flask rises to 65°C, add 9.375g of 20% ammonium persulfate solution and simultaneously add Mix A dropwise using a constant pressure dropping funnel. Control the addition time to complete over 8 hours.
[0062] 6. After the mixed droplet A has been added for 6 hours, the mixed droplet B is added dropwise, and the dripping is controlled to be completed within 4 hours. After the dripping is completed, the mixture is kept warm for 8 hours to terminate the reaction, and the mixture is diluted with water to obtain a 30 wt% aqueous positive electrode edge coating glue.
[0063] The types and amounts of the polymerization monomers used in each embodiment are shown in Table 1.
[0064] Table 1
[0065]
[0066]
[0067] Comparative Examples 1 to 6
[0068] 1. Mixing acrylic acid monomer, acrylamide monomer and hydroxyalkyl acrylate to form a mixed dropwise solution A;
[0069] 2. Mix a double bond monomer, a cross-linking monomer, an emulsifier and water to form a mixed dropwise solution B;
[0070] 3. Prepare 75 g of 20% distilled water solution with 15 g of ammonium persulfate;
[0071] 4. Add 2250 g of distilled water to a 5000 mL four-necked flask, flow nitrogen for 15 minutes, and then heat to 65°C;
[0072] 5. When the temperature of the liquid in the four-necked flask rises to 65°C, add 9.375g of 20% ammonium persulfate solution and simultaneously add Mix A dropwise using a constant pressure dropping funnel. Control the addition time to complete over 8 hours.
[0073] 6. After the mixed droplet A has been added for 6 hours, the mixed droplet B is added dropwise, and the dripping is controlled to be completed within 4 hours. After the dripping is completed, the mixture is kept warm for 8 hours to terminate the reaction, and the mixture is diluted with water to obtain a 30 wt% aqueous positive electrode edge coating glue.
[0074] Comparative Example 7
[0075] 1. Mixing acrylic acid monomer, acrylamide monomer and hydroxyalkyl acrylate to form a mixed dropwise solution A;
[0076] 2. Mix a double bond monomer, a cross-linking monomer, an emulsifier and water to form a mixed dropwise solution B;
[0077] 3. Prepare 75 g of 20% distilled water solution with 15 g of ammonium persulfate;
[0078] 4. Add 1125 g of distilled water to a 5000 mL four-necked flask, flow nitrogen for 15 minutes, and then heat to 65°C;
[0079] 5. When the temperature of the liquid in the four-necked flask rises to 65°C, add 9.375g of 20% ammonium persulfate solution and simultaneously add Mix A dropwise using a constant pressure dropping funnel. Control the addition time to complete over 8 hours.
[0080] 6. Add 1125 g of distilled water to another 5000 mL four-necked flask and purge with nitrogen for 15 minutes before heating to 65°C. When the liquid temperature in the four-necked flask reaches 65°C, add 9.375 g of 20% ammonium persulfate solution. Simultaneously, add Mix B dropwise using a constant pressure dropping funnel. Control the addition time to complete over 8 hours.
[0081] 7. After the liquids in the two reaction bottles have reacted, mix the liquids in the two reaction bottles together and adjust the solid content to 30% to obtain a water-based positive electrode glue.
[0082] The types and amounts of the polymerization monomers used in each comparative example are shown in Table 2.
[0083] Table 2
[0084]
[0085] The properties of the water-based positive electrode edge-coated samples obtained in the above examples and comparative examples were measured.
[0086] The solid content of the sample was adjusted to 30% ± 1%. The solid content was tested using an LHS16-A rapid moisture analyzer with the "115°C, 70s automatic" program selected. The test sample size was 3.5g ± 0.5g, and its solid content was determined.
[0087] Viscosity test: temperature controlled at 25℃, test with Brookfield 62#30r.
[0088] The results of the examples and comparative examples are shown in Table 3.
[0089] Table 3
[0090]
[0091]
[0092] Test Example 1
[0093] The water-based positive electrode side coating glue obtained in the above examples and comparative examples was used in the positive electrode side coating.
[0094] Prepare slurry:
[0095] Slurry formula: 45% water-based positive electrode edge coating glue + 55% boehmite
[0096] Slurry solid content: 30%
[0097] Slurry preparation process: 1. Add 500g of aqueous positive electrode edge coating glue and 350g of water into a 1L beaker, and disperse it at a high speed of 300r / min for 15min; 2. Then slowly add 150g of boehmite into the beaker, being careful not to splash. As the boehmite is added, gradually increase the speed to 1000r / min: 3. Maintain stirring at 1000r / min for 4h, and then filter with a 500-mesh filter cloth to obtain a slurry.
[0098] Slurry testing and coating process:
[0099] 1. Test the slurry viscosity at 25℃, select Brookfield 62#30r for testing, and the viscosity ≤500cp is qualified;
[0100] 2. The slurry is coated with a gravure plate. The current collector is aluminum foil. After coating, it is baked at 80-100°C for 5 minutes to obtain the electrode. The coating thickness is controlled to be 4μm±1μm;
[0101] 3. Fold the electrode 180° in a 15% humidity environment and observe whether the foil is leaking.
[0102] 4. Adhesion to aluminum foil: Use double-sided tape (3M non-woven double-sided tape, width 5cm) to test the adhesion to the aluminum foil. Cut the electrode into 4cm wide strips, stick it to the double-sided tape, roll it back and forth with a 2kg roller, and then pull it at a speed of 2cm / min. Read the number on the tension sensor and multiply the reading by 25 to obtain the adhesion to the aluminum foil in N / m.
[0103] 5. Soak the electrode in 12663 electrolyte (1M LiPF6 EC:DMC:DEC = 1:1:1 (wt%)) at 70°C for 3 days. Remove and wipe the surface with a cotton swab to observe whether the coating has fallen off. Also, test the adhesion to the aluminum foil after soaking with double-sided tape (test method is the same as above).
[0104] The test results are shown in Table 4.
[0105] Table 4
[0106]
[0107]
[0108] Note: If the foil is leaked after wiping 1 to 10 times, it is marked as ☆; if the foil is leaked after wiping 11 to 100 times, it is marked as ☆☆; if the foil is leaked after wiping 101 to 200 times, it is marked as ☆☆☆; if the foil is not leaked after wiping 200 times, it is marked as ☆☆☆☆. " / " means that the force is greater than 200 N / m and the double-sided tape cannot peel off the coating.
[0109] It can be seen that the water-based positive electrode edge coating glue of the present invention has good adhesion to aluminum foil and has certain toughness. There is no foil leakage when folded 180°, and it is not easy to fall off when wiped after being soaked in electrolyte. It can be used in positive electrode edge coating.
Claims
1. Water-based positive electrode edge coating, characterized by: The graft polymer comprises an acrylic polymer as the main chain and grafted polymer latex particles, and the polymer latex particles account for 20 to 80% of the weight of the graft polymer. The polymerization monomers of the acrylic polymer include acrylic acid monomers, acrylamide monomers and hydroxyalkyl acrylate monomers; The polymerization monomers of the polymer latex particles include a cross-linking monomer and a double bond monomer, wherein the double bond monomer includes (meth) alkyl acrylate and at least one of styrene, p-fluorostyrene, methylstyrene, m-fluorostyrene, o-fluorostyrene, p-methoxystyrene, o-methylstyrene, p-methylstyrene, acrylonitrile, and methacrylonitrile.
2. The water-based positive electrode edge coating glue according to claim 1, characterized in that: The weight percentage of the polymer latex particles to the graft polymer is 20% to 50%, and preferably the weight percentage of the polymer latex particles to the graft polymer is 30%.
3. The water-based positive electrode edge coating glue according to claim 1, characterized in that: The acrylic monomer includes at least one of acrylic acid, methacrylic acid, allyloxyhydroxypropyl sulfonic acid, vinyl sulfonic acid, 2-propyleneamine-2-methylpropanesulfonic acid, propylene sulfonic acid, methpropylene sulfonic acid, itaconic acid, and maleic acid; The acrylamide monomer includes at least one of acrylamide, methacrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, 2-methacrylamide, N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, and N-hydroxypropylacrylamide; The hydroxyalkyl acrylate monomer includes at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 2-hydroxy-3-phenoxypropyl acrylate, 3-(4-hydroxyphenoxy)propyl acrylate, 3-(perfluoro-3-methylbutyl) 2-hydroxypropyl acrylate, and 3-perfluorooctyl 2-hydroxypropyl acrylate; The cross-linking monomer includes at least one of ethylene glycol dimethacrylate, ethylene glycol diacrylate, allyl methacrylate, allyl acrylate, N,N-methylenebisacrylamide, and N,N'-methylenebismethylacrylamine; The (meth)acrylic acid alkyl ester includes at least one of n-butyl acrylate, n-butyl methacrylate, n-octyl acrylate, isooctyl acrylate, lauryl methacrylate, lauryl acrylate, octadecyl methacrylate, octadecyl acrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, isobornyl acrylate, vinyl acetate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, glycidyl methacrylate, and glycidyl methacrylate.
4. The water-based positive electrode edge coating glue according to claim 1, characterized in that: The weight ratio of acrylic acid monomer, acrylamide monomer and hydroxyalkyl acrylate monomer is 15-70:1-10:10-30; preferably, the weight ratio of acrylic acid monomer, acrylamide monomer and hydroxyalkyl acrylate monomer is 30-70:1-10:10-20; more preferably, the weight ratio of acrylic acid monomer, acrylamide monomer and hydroxyalkyl acrylate monomer is 57:3:
15.
5. The water-based positive electrode edge coating glue according to any one of claims 1 to 4, characterized in that: Also included is a solvent, which is water.
6. The water-based positive electrode edge coating glue according to claim 5, characterized in that: The viscosity is 80 to 10,000 cp when measured at 25° C. with a solid content of 30%.
7. Use of the water-based positive electrode side coating glue according to any one of claims 1 to 6 in positive electrode side coating.
8. The positive electrode plate edge coating slurry is characterized by: The invention comprises a ceramic material and an adhesive, wherein the adhesive is the water-based positive electrode edge coating adhesive according to any one of claims 1 to 6.
9. The positive electrode edge coating slurry according to claim 1, characterized in that: The ceramic material is selected from at least one of alumina, boehmite, magnesium oxide and magnesium hydroxide.